If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(-2 + -4x) = 156 (-2 * 6 + -4x * 6) = 156 (-12 + -24x) = 156 Solving -12 + -24x = 156 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + -24x = 156 + 12 Combine like terms: -12 + 12 = 0 0 + -24x = 156 + 12 -24x = 156 + 12 Combine like terms: 156 + 12 = 168 -24x = 168 Divide each side by '-24'. x = -7 Simplifying x = -7
| (-1)(7)= | | 3x^2+7-2=0 | | 1-4x-3x=-6 | | 36=4*4 | | 36=4*7 | | 3cos(x)+4sin(x)=2 | | 14+8z=-14+8z | | 20r^2+7=45r+7 | | 4(5+2b)=12 | | 36=4*6 | | 1+3n=16 | | 133=-13p | | 12-x=167 | | (x^3+6x^2+11x+6)=(x^2+4x+3) | | -2-5v=3 | | -5+4n=-29 | | 9=2(x+5)-3(x-4)-10 | | (6y+8)-(5+5y)=4 | | 8x+14y-12+10=0 | | -2-2b=0 | | 5(7+p)=10 | | 27m^6-512=0 | | 2x*4=46 | | 5a+3a+8a=16a | | 5x+50=x-34 | | (3x+7)(7x+3)=0 | | y=(-3-8)(-3+2) | | A-(-5)=1 | | X=A-12 | | 8h+5-3h=8h | | 0=(-3-8)(-3+2) | | 3y-9=-27+9y |